2021
DOI: 10.4012/dmj.2020-273
|View full text |Cite
|
Sign up to set email alerts
|

In-air micro-proton-induced X-ray/gamma-ray emission analysis of the acid resistance of root dentin after applying fluoride-containing materials incorporating calcium

Abstract: This study employed an in-air micro-proton-induced X-ray/gamma-ray emission system to assess the effectiveness of fluoridecontaining materials (FCMs) incorporating calcium in preventing root caries. Dentin surfaces of human third molars were coated with one of three FCMs: fluoride-releasing glass-ionomer cement (F7) and experimental materials in which half (P1) or all (P2) of the strontium in F7 was replaced with calcium. Dentin without FCM coating served as the control. Specimens were immersed in saline at 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Our previous study had shown that calcium fluoride-like deposits may form on the root surface after application of fluoride-containing cements incorporating calcium 18) . Many studies have also identified calcium fluoride-like deposits as the most important reversible source of fluoride on the tooth surface [36][37][38][39][40] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study had shown that calcium fluoride-like deposits may form on the root surface after application of fluoride-containing cements incorporating calcium 18) . Many studies have also identified calcium fluoride-like deposits as the most important reversible source of fluoride on the tooth surface [36][37][38][39][40] .…”
Section: Discussionmentioning
confidence: 99%
“…Regular application of varnish as professional care, in addition to the use of fluoridecontaining toothpaste for self-care, can further enhance its preventive effect on root surface caries 17) . In our previous report 18) , we found that fluoride-containing filling materials that incorporate calcium significantly improve the acid resistance of root dentin and could prevent root caries. Moreover, the addition of calcium to glass ionomer cements reduced mineral loss when immersed in a demineralizing solution, and the uptake of fluoride ions into the dentin was not altered.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…4). For (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) nA change in proton current, cps ( 181 Ta(p,p ′ g) 181 Ta) varied linearly within a small range (5-60 cps), whereas for N(p,p ′ g) 14 N, cps increases with increasing beam current up to 10 nA, aer which no such signicant variation in cps was observed. This ensured that N 2 from air could be used as effective current normalizer in the external PIGE method with uctuations in proton current from (5-10) nA.…”
Section: Optimization Of the External Pige Methods For Uorine Quanti...mentioning
confidence: 94%
“…13,14 Low Z elements, like phosphorus, have been quantied directly on solid samples by electrothermal vaporization-inductively coupled plasma atomic emission spectrometry. 15 In recent years, Particle Induced Gamma-ray Emission (PIGE) 16,17 or Micro-PIGE 18 is a well-known nuclear analytical technique for uorine determination in solid matrices. PIGE is such an online nuclear analytical technique where accelerators are used for nuclear reactions like (p,p ′ g), (p,ag) or (p, ng).…”
Section: Introductionmentioning
confidence: 99%